Infrastructure Development and Its Effects on Transport, Demography and Employment: The Example of a New Rail Line Dresden–Prague. - Heldt, Petra (My University, 2019)
This report describes the relation between the core network corridor Orient/EastMed and the elimination of one serious bottleneck with the example of the planned new railway line Dresden–Prague. In cooperation between the Free State of Saxony and the Czech Republic first preplanning studies were elaborated for a new cross border track, which will bring the regions closer together and has positive effects for a modal shift to rail as well as for the regional economy and development. The basis of this report are results of the study for the new line from 2015. An incorporation of interim new proposals for a route guidance has not been made due to the lack of depth of investigation of these alternatives at the moment.

Der Beitrag verdeutlicht den Zusammenhang zwischen dem Kernnetzkorridor Orient/ East-Med und der Beseitigung eines gravierenden Engpasses am Beispiel der geplanten neuen Eisenbahnstrecke Dresden-Prag. In Zusammenarbeit des Freistaates Sachsen und der Tschechischen Republik wurden erste Vorplanungsstudien für eine neue grenzüberschreitende Strecke erarbeitet, die die Regionen näher zusammenbringt und positive Auswirkungen auf eine Verkehrsverlagerung auf die Schiene sowie auf die regionale Wirtschaft und Entwicklung hat. Grundlage dieses Beitrags sind die Ergebnisse der Studie für die neue Linie von 2015. Zwischenzeitlich neu vorgeschlagene Routenführungen wurden nicht aufgenommen, da diese Alternativen bislang nicht gründlich genug geprüft werden konnten.
Infrastrukturentwicklung und ihre Auswirkungen auf Verkehr, Demographie und Beschäftigung: Das Beispiel einer neuen Eisenbahnstrecke Dresden–Prag.
Keywords: Verkehrsnetz; Grenzüberschreitender Verkehr; Schienenverkehr; Verkehrskorridor; Verkehrsverlagerung; Güterverkehr; Streckenführung; Europäische Zusammenarbeit; Verkehrsentwicklungsplanung